Formação crítica de professores: o registro de uma experiência - Cardoso, Karina Cristina de Azevedo (2017)
The present research aims to critically analyze the continuous teacher education activities prepared for the course "Classroom Management: a real and possible challenge!", applied to teachers and pedagogical coordinators from Mogi das Cruzes in 2013. The study is based on a critical, collaborative and creative perspective that, in general terms, profess the deconstruction of common sense discourse, opening space for a reflexive conscience, which requires the participants shared responsibility, commitment and improvement, so that the professionals involved discuss and look for solutions to the daily school demands (LIBERALI; FUGA, 2014). In addition, this discussion is enriched by the theoretical dialogue among several researchers (IMBERNÓN, 2000; LIBERALI, 2008; MARCELO, 2008; NÓVOA, 2009; PLACCO; SOUZA, 2006), who share that reflection on educational practice teacher education. For these researchers, the partnership relation between the coordinating teacher and teachers, influences the practice in the classroom. The critical research of collaboration (PCCol) (MAGALHÃES, 2004) grounds methodologically this paper, when proposing a space for critical reflection toward the transformation from the collaborative practice among participants. To reach the objective of this paper, three activities are analyzed, considering its degree of complexity. For this, the critical reflection stages - Describing, Informing, Confronting and Reconstructing (SYMITH, 1992) - are considered categories of analysis, besides the theoretical frame as a guiding parameter for its interpretation. The analytical discussion allows the activities redefinition with a more collaborative and participatory perspective, which makes the course "Classroom Management: a real and possible challenge!" a formative action that can be shared with other teachers who work with teacher education. The results seem to indicate a critical, collaborative and creative bias in the elaboration of formative activities, in which the context needs to be considered and the dialogue between theory and practice effectively put into practice in the re-signification of activities